GLOBAL MANAGEMENT AND GLOBAL CULTURE: A BIBLIOMETRIC REVIEW OF BUSINESS PRACTICES AND PERFORMANCE - Asmaraningtyas, Lussy Widia; Sriyono, Sriyono (STKIP Persada Khatulistiwa Sintang, 2024)
This research discusses Global Management and Global Culture in the context of international business development. Through a bibliometric approach, this research evaluates related literature to understand the influence of global management and global culture on business practices and company performance. The main findings highlight publication trends that include digitalization, sustainability, diversity, and the concept of